Seminar on Future Trends and Research in the Field of Study Smart Learning Environment - Erlangga, Erlangga; Rahman, Eka Fitrajaya; Putro, Budi Laksono; Junaeti, Enjun; Piantari, Erna; Judie, Rizky Rachman; Rasim, Rasim (Universitas Pendidikan Indonesia, 2023)
The field of education has advanced thanks to technological developments in the 21st century. Teaching and learning activities have pointed towards a smart learning environment (SLE). Many research efforts have attempted to define SLE as well as identify key features for creating an intelligent learning environment. SLE is a development of digital learning environments (DLEs). Both SLE and DLEs have the same goal, which is to provide an effective, efficient and attractive learning environment for learners. The purpose of this community service is to introduce SLE research and studies, provide insight to academics, practitioners and students regarding SLE research trends, find out the extent of implementation, needs and opportunities for SLE implementation in institutions. The method used is the direct communication counseling method by holding webinars (online seminars) regarding SLE research trends targeting academics, practitioners and students at both undergraduate and postgraduate levels. At the end of the activity, a question-and-answer session was carried out, and the participants filled out a questionnaire as a form of evaluation. After attending this seminar, it is expected that the participants can understand trends future research regarding the field of SLE studies.